IMPLEMENTASI PENDIDIKAN INKLUSI DI PROVINSI RIAU BERDASARKAN PERATURAN DAERAH PROVINSI RIAU NOMOR 18 TAHUN 2013 TENTANG PERLINDUNGAN DAN PEMBERDAYAAN PENYANDANG DISABILITAS - Khofifah Hasanah Pane; Emilda Firdaus; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Disability comes from the absorption of the English word "disability or disabilities" which describes an inability or deficiency that exists both physically and mentally, which causes the sufferer to be limited in carrying out an activity. Persons with disabilities are entitled to all sectors of life. Furthermore, specifically related to education, every person with disabilities has the same opportunity and treatment to obtain inclusive education in units, pathways, types and levels of education according to the type and degree of their disability. In the framework of protecting and empowering persons with disabilities, Riau Province itself has Regional Regulation Number 18 of 2013 concerning the Protection and Empowerment of Persons with Disabilities. The objectives of this thesis are: First, the implementation of inclusive education in Riau Province based on Riau Province Regional Regulation Number 18 of 2013 concerning the Protection and Empowerment of Persons with Disabilities. Second, the inhibiting factor of the implementation of inclusive education in Riau Province. Third, efforts are made to address the problems of inclusive education in Riau Province.This type of research is sociological legal research, because it is based on field research, namely by collecting data from interviews, questionnaires, and literature reviews that are related to the problems to be studied assisted by primary, secondary and tertiary data. This research was conducted at the Regional Representative Council of Riau Province, Riau Provincial Education Office, Riau Province Social Service, while the population and sample were all parties related to the problem under study. This study uses qualitative data analysis and produces descriptive data.From the research results it can be concluded that, First, the implementation of inclusive education in Riau Province has not been running optimally. Second, the inhibiting factors of the implementation of inclusive education are budget, human resources as teaching staff, infrastructure, school willingness, and lack of socialization and supervision. Third, the efforts made to overcome these inhibiting factors are making local regulations related to persons with disabilities, allocating budgets for inclusive education, increasing human resources as educators for people with disabilities, preparing schools through facilities and infrastructure as well as providing education and outreach and also carrying out adequate supervision optimal.Keywords: Implementation- Regional Regulations-Inclusive Education